2019
DOI: 10.1101/824078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of G-protein coupled estradiol receptor 1 in the dorsolateral striatum attenuates preference for cocaine and saccharin in male but not female rats

Abstract: There are sex differences in susceptibility to addiction. Cultural influences play a role in drug seeking behaviors; however, sex differences are found in rodent models of addiction as well, suggesting that there are also neurobiological factors involved. Extensive research has shown that estradiol facilitates enhanced motivation and drug seeking in female but not male rodents.Estradiol treatment also potentiates cocaine induced dopamine overflow in the dorsolateral striatum (DLS) of females. Together, these f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We also identified upstream regulators that may have sex-specific roles in the VTA. For example, pharmacological studies suggest that ER-alpha activity, one upstream regulator we identified from both HC Chronic and IVSA samples, is protective against the effects of cocaine in males, but promotes cocaine action in females [69]. Examining the putative downstream targets of ERalpha that we identified in our datasets within both males and females may provide new insight into the sex-dependent roles of ER-alpha in response to cocaine.…”
Section: Discussionmentioning
confidence: 86%
“…We also identified upstream regulators that may have sex-specific roles in the VTA. For example, pharmacological studies suggest that ER-alpha activity, one upstream regulator we identified from both HC Chronic and IVSA samples, is protective against the effects of cocaine in males, but promotes cocaine action in females [69]. Examining the putative downstream targets of ERalpha that we identified in our datasets within both males and females may provide new insight into the sex-dependent roles of ER-alpha in response to cocaine.…”
Section: Discussionmentioning
confidence: 86%